2020
DOI: 10.1093/brain/awaa018
|View full text |Cite|
|
Sign up to set email alerts
|

Recommendations to distinguish behavioural variant frontotemporal dementia from psychiatric disorders

Abstract: The behavioural variant of frontotemporal dementia (bvFTD) is a frequent cause of early-onset dementia. The diagnosis of bvFTD remains challenging because of the limited accuracy of neuroimaging in the early disease stages and the absence of molecular biomarkers, and therefore relies predominantly on clinical assessment. BvFTD shows significant symptomatic overlap with non-degenerative primary psychiatric disorders including major depressive disorder, bipolar disorder, schizophrenia, obsessive-compulsive disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
234
0
23

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 208 publications
(269 citation statements)
references
References 192 publications
12
234
0
23
Order By: Relevance
“…NfL is the most promising fluid biomarker for diagnostics and monitoring degeneration in FTD both in the context of clinical practice as well as in clinical trials [ 33 ] In the diagnostic process, NfL is the only fluid biomarker with potential to separate bvFTD from psychiatric disorders [ 34 , 35 ], which constitute the main differential diagnosis for bvFTD [ 36 ]. Plasma is arguably preferable to CSF for NfL measurements due to the minimally invasive procedure required to sample it.…”
Section: Discussionmentioning
confidence: 99%
“…NfL is the most promising fluid biomarker for diagnostics and monitoring degeneration in FTD both in the context of clinical practice as well as in clinical trials [ 33 ] In the diagnostic process, NfL is the only fluid biomarker with potential to separate bvFTD from psychiatric disorders [ 34 , 35 ], which constitute the main differential diagnosis for bvFTD [ 36 ]. Plasma is arguably preferable to CSF for NfL measurements due to the minimally invasive procedure required to sample it.…”
Section: Discussionmentioning
confidence: 99%
“…As well as difficulties in differentiating FTD from AD clinically on occasion, there can also be problems with differentiating FTD from non-neurodegenerative disorders at times, including those with primary psychiatric disorders. Recent studies have shown that changes in non-specific markers of degeneration (such as neurofilament light chain protein (NfL) [Box 3]) may be helpful in this setting 33,34 .…”
Section: Differentiating Ftd From Other Dementias and From Non-degenementioning
confidence: 99%
“…Frontotemporal dementia (FTD) is known to have distinct clinical features from Alzheimer's disease (AD), developing behavioral and language symptoms with relatively preserved memory function (Ducharme et al, 2020;Neary et al, 1998;Rascovsky et al, 2011). Patients with FTD particularly tend to show distinctive unusual behaviors such as disinhibition, loss of social awareness, overeating, perseverative and stereotyped behavior, and impulsivity which are often antisocial (Ikeda, 2007;Neary et al, 1998;Rascovsky et al, 2011).…”
mentioning
confidence: 99%